Acetolactate synthase activity in Euphorbia heterophylla resistant to ALS- and protox- inhibiting herbicides - Xavier,E. (2013)
The objective of this study was to determine the activity of the enzyme acetolactate synthase in biotypes of wild poinsettia (Euphorbia heterophylla) with multiple resistance to ALS- and Protox- inhibitors in the presence and absence of imazapyr, imazethapyr and nicosulfuron. We conducted in vitro assay of ALS enzyme extracted from plants of Vitorino, Bom Sucesso do Sul and Medianeira biotypes (with multiple resistance) and a susceptible population in the absence and presence of imazapyr, imazethapyr and nicosulfuron. In the absence of herbicides, biotypes with multiple resistance showed higher affinity for the substrate of the enzyme compared with the susceptible population. The herbicides imazapyr, imazethapyr and nicosulfuron had little effect on the enzyme activity of ALS-resistant biotypes and, conversely, high inhibitory effect on ALS of the susceptible population. Resistance factors were very high, greater than 438, 963 and 474 for Vitorino, Bom Sucesso do Sul and Medianeira biotypes, respectively. The resistance to ALS inhibitors is due to the insensitivity of ALS to herbicides of both imidazolinone and sulfonylurea groups, characterizing a cross-resistance.